Evaluating chronic disease management : recommendations for funders and users - Nolte, Ellen (Technical report (Rand Corporation), 2012)
The report forms part of the DISMEVAL project, funded under the European Commission's 7th Framework Programme. It is targeted at policymakers, programme operators and researchers, explaining choices, options and trade-offs for the evaluation of disease management based on analyses undertaken within the project. Many of the issues discussed can be seen to apply to any evaluation of complex interventions in healthcare. However, there are specific concerns around evaluation design and metrics that are of relevance to the evaluation of disease management in particular and that are examined in the report. These include (i) the context for evaluating disease management, exploring the reasons for undertaking evaluation in the first place and explaining some of the underlying principles for doing so; (ii) the methods and metrics for evaluating disease management, focusing specifically on themes that have emerged as being pertinent to work carried out within the DISMEVAL project; (iii) practical considerations for disease management evaluation, based on experience of work undertaken in DISMEVAL; and (v) the broader challenges and lessons learned that may be relevant for policymakers, funders and practitioners interested in the use and usefulness of disease management evaluation more generally. This publication provides a major resource to guide the evaluation of disease management interventions in European settings and so contributes to strengthening the evidence-base required to inform the selection of efficient and effective interventions to address the growing burden of chronic disease in Europe.